추출방법에 따른 인삼씨유의 품질특성 - 김지은(Ji-Eun Kim); 이슬(Seul Lee); 유경미(Kyung-Mi Yoo); 이경혜(Kyoung-Hae Lee); 김경탁(Kyung-Tack Kim); 이명희(Myung-Hee Lee); 황인경(In-Kyeong Hwang) (Han'guk Sikp'um Yŏngyang Kwahakhoe chi, 2014)
This study aimed to determine the quality characteristics of ginseng seed oil as well as evaluate the efficacy of ginseng seed oil as a food resource. Ginseng seed oil was obtained by different extraction methods; from solvent extraction oil, supercritical fluid extraction oil, and screw pressed extraction oil. Total unsaturated fatty acids were present at 97.72~97.92%. Oleic acid (80.13~81.16%) was the highest, followed by linoleic acid (14.98~15.69%). The total phenol content (mg gallic acid equivalent/100 g oil) was higher in screw pressed extraction oil ($56.32{±}1.47$) compared to others. ${γ}$-Tocopherol was only present in ginseng seed oil and screw pressed extraction oil showed the highest levels of ${γ}$-tocopherol ($5.95{±}0.25$ mg/100g oil) among the tested samples. Screw pressed extraction oil showed the greatest oxidative stability with an induction time of 16.58 hours. Acid values and peroxide values of ginseng seed oil increased with increasing storage period. The total phenol and ${γ}$-tocopherol contents were higher in screw pressed extraction oil than in other ginseng seed oils, which suggests that screw pressed extraction oil has the greatest oxidative stability. 본 연구에서는 추출방법에 따른 인삼씨유(ginseng seed oil)의 이화학적 품질특성과 저장 중 산화안정성을 살펴보았다. 인삼씨유를 용매추출, 초임계유체추출, 압착추출 방법으로 추출한 결과 초임계추출 한 인삼씨유의 수율이 가장 높았다. 인삼씨유의 L값은 8.70~11.38의 범위였고, a값은 초임계유체추출 오일 처리구에서, b값은 압착추출 오일에서 유의적으로 크게 나타났다. 지방산 조성은 불포화지방산이 대부분을 차지했으며, oleic acid(C18:1)의 함량이 80.13~81.16%로 가장 많았고 linoleic acid(C18:2)는 14.98~15.69%를 차지했다. 인삼씨유의 포화지방산으로는 유일하게 palmitic acid(16:0)만 검출되었다. 총 폴리페놀 함량은 압착추출 오일이 $56.32{±}1.47$ mg GAE/100g oil로 가장 높게 나타났다. 인삼씨유에서는 ${γ}$-토코페롤만 검출되었으며, 압착추출 오일의 ${γ}$-토코페롤 함량이 $56.32{±}1.47$ mg GAE/100g oil로 가장 높았다. 인삼씨유의 토코페롤 산화 유도시간은 압착추출 오일이 16.58시간으로 가장 길게 나타났다. 인삼씨유의 산가와 과산화물가는 저장기간에 따라 모두 증가하는 경향을 나타냈다. 결과적으로 압착추출 오일의 산화안정성이 가장 우수하게 나타났으며, 이는 항산화 활성을 지닌 총 페놀함량과 ${γ}$-토코페롤 함량이 초임계유체추출 오일과 용매추출 오일에서보다 압착추출 오일에서 가장 높게 나타났기 때문이라 판단된다.